Trouver le chemin de la grâce : les villes rebelles et leurs stratégies pour rétablir le dialogue avec le souverain (royaume de France, seconde moitié du XVe siècle) - Adrien Carbonnet (Criminocorpus)
Repression of urban uprisings in the second half of the 15th century gave rise to negotiations between the king and the city. However, the search for agreement is rarely mentioned in the documentation. In fact, in the sources, a discourse dominates according to which the revolt is an offense to the king, and therefore to God. From then on, no agreement is possible between the sovereign and those who are presented as rebels. The city, penitent, must then seek the grace of the sovereign. However, the analysis of the sources of the practice reveals a part of negotiations in this search for royal pardon. The cities elaborate complex strategies to obtain a way out of the crisis.